Plasma Proteomics for Epidemiology: Increasing Throughput With Standard-Flow Rates. (December 2017) - Yin, Xiaoke; Baig, Ferheen; Haudebourg, Eloi; Blankley, Richard T.; Gandhi, Tejas; Müller, Sebastian; Reiter, Lukas; Hinterwirth, Helmut; Pechlaner, Raimund; Tsimikas, Sotirios; Santer, Peter; Willeit, Johann; et al.
Abstract : Background—: Mass spectrometry is selective and sensitive, permitting routine quantification of multiple plasma proteins. However, commonly used nanoflow liquid chromatography (LC) approaches hamper sample throughput, reproducibility, and robustness. For this reason, most publications using plasma proteomics to date are small in study size. Methods and Results—: Here, we tested a standard-flow LC mass spectrometry (MS) method using multiple reaction monitoring for the application to large epidemiological cohorts. We have reduced the LC-MS run time to almost a third of the nanoflow LC-MS approach. On the basis of a comparison of the quantification of 100 plasma proteins in >1500 LC-MS runs, the SD range of the retention time during continuous operation was substantially lower with the standard-flow LC-MS (<0.05 minutes) compared with the nanoflow LC-MS method (0.26–0.44 minutes). In addition, the standard-flow LC method also offered less variation in protein measurements. However, 5× more sample volume was required to achieve similar sensitivity. Two different commercial multiple reaction monitoring kits and an antibody-based multiplexing kit were used to compare the apolipoprotein measurements in a subset of samples. In general, good agreement was observed between the 2 multiple reaction monitoring kits, but some of the multiple reaction monitoring–based measurements differed from antibody-based assays. Conclusions—: The multiplexing capability of LC-MS combined with a standard-flow method increases throughput and reduces the costs of large-scale protein measurements in epidemiological cohorts, but protein rather than peptide standards will be required for defined absolute proteoform quantification. Abstract : Supplemental Digital Content is available in the text.